Pharmacokinetics of fostamatinib, a spleen tyrosine kinase (SYK) inhibitor, in healthy human subjects following single and multiple oral dosing in three phase I studies. (20th June 2013) - Baluom, Muhammad; Grossbard, Elliott B.; Mant, Tim; Lau, David T. W.
<x xml:space="preserve">Abstract</x> Aim Fostamatinib (R788) is an orally dosed prodrug designed to deliver the active metabolite R940406 (R406), a spleen tyrosine kinase (SYK) inhibitor, for the treatment of rheumatoid arthritis. The objectives were to evaluate the human pharmacokinetic properties of fostamatinib and R406. Method Three clinical studies were conducted in healthy subjects: (A) A single ascending dose study for R406 with doses ranging from 80–600 mg, (B) a single‐ and multiple‐dose study of fostamatinib in aqueous suspension, with single doses ranging from 80–400 mg and multiple doses at 160 mg twice daily and (C) a study comparing suspension and tablet of fostamatinib, with the latter tested in both fed and fasted states. Results These studies demonstrated that when administered as a solution, R406 was rapidly absorbed. Increases in exposure were observed with doses up to 400 mg. A terminal half‐life of 12–21 h was observed. Similar R406 exposure could be achieved with fostamatinib suspension and steady‐state was achieved after 3–4 days following twice daily administration. Fostamatinib tablet and suspension exhibited similar R406 exposure. Upon co‐administration with food, a delay in peak time and lower peak concentrations of R406 were observed but at the same time the overall exposure did not change. Conclusion Fostamatinib demonstrates rapid and extensive conversion to R406, an inhibitor of SYK. Solid dosage forms of fostamatinib overcome the challenge of low aqueous solubility of R406. The PK profile of R406 could potentially allow once daily or twice daily oral administration of fostamatinib.